The Effect of Corporate Governance and Financial Performance on Dividend Policy - Rochmah Yuniati; Anita Wijayanti; Riana Rachmawati Dewi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to examine and analyze the effect of corporate governance and financial performance on dividend policies. The dependent variable is dividend policy and the independent variable is the size of the board of commissioners, independent board of commissioners, managerial ownership, liquidity and profitability. The population of this research is 14 Manufacturing companies listed on the Indonesia Stock Exchange in the period 2015 – 2018. With a total sample size of 56 and this sampling technique uses a purposive sampling method. Testing the hypothesis of this study using multiple linear regression test. The results of this study indicate that the size of the board of commissioners, the board of independent commissioners and profitability affect the dividend policy, managerial ownership and liquidity do not affect the dividend policy